Em busca do tempo perdido de Marcel Proust recriado em quadrinhos: o narrador de No caminho de Swann adaptado para narrativas gráficas - Espúrio, Karina [UNESP] (2015)
This study offers a critical discussion on the graphic novel adaptation of the first volume of Marcel Proust's In Search of Lost Time: Swann's Way, by Stéphane Heuet. It aims to look into the relationship between the first volume of the Recherche and its graphic novel version in order to analyse how the narrator from Proust's novel was recreated through the uses of images and words in Heuet's text. Bearing that in mind, the present research uses Linda Hutcheon's reflections on adaptation in A Theory of Adaptation as its theoretical background. In the end, the hypothesis investigated is that images and words are interdependent in Heuet's work